2020
DOI: 10.30996/dia.v18i2.3654
|View full text |Cite
|
Sign up to set email alerts
|

Poor Aceh: The Impact of Special Autonomy as Effort Poverty Reduction in Aceh

Abstract: Special autonomy as one of the strategies in overcoming social welfare issues is one of them in Aceh Province. The implementation of regional autonomy after the reforms marked by the issuance of Law Number 33 of 2004 concerning the financial balance between the central government to the regions. The hope is to make the regions more autonomous or independent in government, and a more equal financial structure and the right to manage financial resources that are more transparent. This research focuses on the imp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 0 publications
0
5
0
1
Order By: Relevance
“…This is reinforced by Mahendra (2017), who stated that econo mic growth as the effect of government spending affects the number of poor people. Setiawan et al, (2020), found the same thing which shows that special autonomy has an influence in reducing poverty in Aceh.…”
Section: Source: Bps 2020mentioning
confidence: 69%
“…This is reinforced by Mahendra (2017), who stated that econo mic growth as the effect of government spending affects the number of poor people. Setiawan et al, (2020), found the same thing which shows that special autonomy has an influence in reducing poverty in Aceh.…”
Section: Source: Bps 2020mentioning
confidence: 69%
“…Eco-tourism hutan mangrove yang terletak di Sayeung Desa Baro, Kecamatan Setia Bakti Kabupaten Aceh Jaya berperan aktif dalam pengurangan angka pengangguran dan kemiskinan, dengan tetap menekankan pada situasi yang ramah lingkungan (Snyman, 2017), artinya tidak sporadis hanya berorientasi pada profit saja namun tetap memperhatikan lingkungan demi keberlanjutan hutan mangrove tersebut. Saat ini, menurut data Badan Pusat Statistik (2022) tingkat pengangguran terbuka di Kabupaten Aceh Jaya dalam beberapa tahun terakhir ini tergolong cukup tinggi yaitu berada pada angka 4.19 (2019), 4.08 persen (2020), dan 3.47 (2021) (Setiawan, Ulfa and Purwaningsih, 2020). Kondisi tersebut menjadikan ecotourism mangrove memiliki peluang untuk menyerap angka pengangguran bagi banyak lapangan pekerjaan terbuka dan mampu menjadi salah satu upaya dan strategi penanggulangan kemiskinan di Kabupaten Aceh Jaya.…”
Section: Pendahuluanunclassified
“…This should have had more impact on the welfare of people in Aceh. However, during the period of implementation of this policy, the poverty rate in Aceh was still quite high (Hasta Budiratna & Riatu M. Qibthiyyah, 2020;Setiawan et al, 2020).…”
Section: Introductionmentioning
confidence: 99%